Attenuation of Neuronal Tissue Damage in Ischemic Stroke by Tat-NR2Bct-CTM and Tat-NR2B9c - Benedictus Benedictus; Kenneth Tan; Vincent Kurniawan Putra Pratama; Jonathan Daniel Sulastyo (Magna Neurologica, 2023)
Background: Worldwide, stroke accounts for 15 million cases annually. Despite improved understanding of its pathophysiology, an effective treatment is yet to be available. Objective: This review aims to expound ischemic stroke pathophysiology from a bio-molecular perspective, and present two peptides, namely Tat-NR2B9c and Tat-NR2Bct-CTM, which has been proven to attenuate neuronal tissue damage in ischemic stroke. Methods: Scoping review of several electronic databases: PubMed, Medline, Researchgate, NCBI, SpringerLink, and Google scholar. Search query included: ischemic stroke, NR2B, DAPK1, nNOS, NOX, Tat-NR2Bct-CTM and Tat-NR2B9c. Results:  It is recognizable in a sense, that the pathophysiology pivots on the NR2B-DAPK1 and PSD-95-NR2B interactions. Tat-NR2Bct-CTM and Tat-NR2B9c thwarts NR2B-DAPK1 and PSD-95-NR2B interactions, respectively. These peptides show significant reliability, with the former capable of reducing free DAPK1 by 92,85%, and the latter, the first stroke treatment in two decades to reach Phase 3 clinical trials. Conclusion: These results strongly support Tat-NR2Bct-CTM and Tat-NR2B9c as effective means to reduce neuronal tissue damage in ischemic stroke.